Indoor Summer Thermal Comfort in a Changing Climate: The Case of a Nearly Zero Energy House in Wallonia (Belgium) - Olivier Dartevelle; Sergio Altomonte; Gabrielle Masy; Erwin Mlecnik; Geoffrey van Moeseke (Energies, 2022)
While the potential impact of climate change mitigation measures is well documented in building sciences literature, there are only relatively sparse studies focusing on the efficiency of adaptation strategies. This paper aims to contribute to this topic by evaluating the extent to which the design of a typical nearly Zero Energy Buildling (nZEB) house in Wallonia (Belgium), and its current operation, could provide summer thermal comfort in a changing climate. Based on calibrated whole building energy simulations, and on the integration of future climate data directly derived from a high-resolution climate model, this study evaluates the potential evolution of overheating risks in the living room and in the main bedroom of the house. Discussing the compliance with existing overheating criteria, the study shows that the passive strategies currently deployed in the house might not be sufficient to guarantee summer thermal comfort especially in the bedroom, and that other strategies might be necessary in the future to limit the use of active cooling systems and curb their environmental impacts. This study concludes that considering the potential of these strategies to guarantee summer thermal comfort in a changing climate should be a priority for the design of nZEB houses (and their related policies) also in temperate oceanic climates.